Relationships between differential aptitude tests scores and grades in science subjects in the U.P. Preparatory School (Manila) - Rabago, Lilia (Malabonga) 1933- (s.n.], 1963)
This study provides tools for classifying science students in the UP Preparatory School into homogeneous classes to facilitate instruction and the means of predicting their accomplishment in the science subject based on their potentials.